AN ANALYSIS ON POST-MERGER PROFITIBILITY OF THE SHAREHOLDER OF THE ACQUIRING FIRM - Banerjee, Lisha (2010)
Mergers and acquisition have been an crucial element of strategy in the corporate world for several years. The question whether mergers create a substantial gain in the short and the long-run still remains a puzzle. As per the existing literature on the post-merger performance of acquiring firms there still remains conflicting views. Thus the debate continues on the consequence of mergers and acquisition firms. My research puts in an effort to examine the shareholders wealth effects in short-run of the bidding firm. The research compiles the sample size of 147 companies covering USA acquirer between the year 2000-2005. The bidder uses different targets like public and private and methods of payment. Therefore any variation in the returns of the bidder must be due to the characteristics of the targets or the mode of payment. The results indicate that the acquiring firm shareholder gain on buying private targets whereas they lose on public targets. In order to understand the variations in the returns of bidder various related factors have been selected surrounding the announcement date. However there is no major significance of any factor on the abnormal returns in this study due to the bidder size being very large compared to the target. The research focuses on the target type as the crucial parameter for impacting the returns.